Study on pump optimizing for Bi/Er co-doped optical fiber. (February 2016) - Ni, Jiasheng; Peng, G.D.; Wang, Chang; Luo, Yanhua; Xiao, Gui; Wei, Shuen; Liu, Han; Liu, Tiegen
Abstract: Bi/Er co-doped optical fiber is one of the solutions for wave band extending technology which is very important for fiber amplifiers, lasers and communication system. Pump option can alter emission band of the Bi/Er co-doped fiber. In this paper, optimization of pump wavelength is proposed. A high Bi concentration co-doped Bi/Er optical fiber is tested as a sample to demonstrate pump wavelength influence to the emission spectrum band. An optical fiber measurement system is provided to measure out characteristics of active optical fibers. And some useful results and parameters of pump optimizing for Bi/Er co-doped optical fiber are discussed in detail. From this research, optimized pump wavelength is suggested around 1350 nm to get a wider continue spectrum covers from 1300 nm to 1600 nm.